2013
DOI: 10.4236/me.2013.412086
|View full text |Cite
|
Sign up to set email alerts
|

Do Higher Tax Rates Encourage/Discourage Tax Compliance?

Abstract: In this survey, we try to summarize what economists know about how increasing tax rate affects both tax evasion and the willingness to pay taxes. We show how this apparently trivial question presents puzzling results. This paper introduces the main contributions that have attempted to explain the apparent contradiction between the empirical evidence on the reaction of taxpayers to changes in tax rate levels and the results obtained by the standard models of tax evasion. In an effort to shed some light on this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
2
14
2
Order By: Relevance
“…Sales tax rate is defined in the present study as the percentage imposed on goods and services supplies, regardless whether they are imported from abroad or from free zones, and local producers if the supply is taxable by sales tax law. Prior studies showed a significant negative relationship between tax rate and tax compliance (Kim, 2008;Ali, Cecil, & Knoblett, 2001), while some evidenced no significant relahip (e.g., Pellizzari & Rizzi, 2014;Seren & Panades, 2013). On a contrasting finding, Alm, Sanchez and Juan (1995) and Yitzhaki (1974) supported a positive relationship between increased rate of tax and increased tax compliance.…”
Section: Determinants Of Sales Tax Compliancementioning
confidence: 98%
“…Sales tax rate is defined in the present study as the percentage imposed on goods and services supplies, regardless whether they are imported from abroad or from free zones, and local producers if the supply is taxable by sales tax law. Prior studies showed a significant negative relationship between tax rate and tax compliance (Kim, 2008;Ali, Cecil, & Knoblett, 2001), while some evidenced no significant relahip (e.g., Pellizzari & Rizzi, 2014;Seren & Panades, 2013). On a contrasting finding, Alm, Sanchez and Juan (1995) and Yitzhaki (1974) supported a positive relationship between increased rate of tax and increased tax compliance.…”
Section: Determinants Of Sales Tax Compliancementioning
confidence: 98%
“…However, from a more rigorous theoretical perspective, it can be hypothesised that the effect of an income tax rate change on income tax evasion is actually ambiguous (Crane and Nourzad, 1986;Caballé and Panadés, 2007;Gahramanov, 2009;Freire-Serén and Panadés, 2013). The sign on the partial derivative of tax evasion with respect to the income tax rate theoretically depends upon the relative strengths of the substitution effect associated with the tax rate change on the one hand and the income effect associated with the tax rate change on the other hand.…”
Section: Expected Direct Benefits Of Under-reporting Taxable Incomementioning
confidence: 99%
“…Among the types of information thusly obtained and analysed are data on income tax evasion, income tax rates, penalties assessed on detected unpaid income taxes and audit rates. Such studies endeavour typically either seek to estimate the relative extent of tax evasion or to identify determinants thereof (Tanzi, 1982;Clotfelter, 1983;Carson, 1984;Crane and Nourzad, 1987;Poterba, 1987;Pyle, 1989;Erard and Feinstein, 1994;Feige, 1994;Joulfaian and Rider, 1996;Cebula, 1997;2004;2011;2013;Ali et al, 2001;Alm and Yunus, 2009;Cebula et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… See, for example, Allingham and Sandmo (), Yitzhaki (), Slemrod and Yitzhaki (). See Freire‐Serén and Panadés () for a review of the literature.…”
mentioning
confidence: 99%